The effect of anxiety, depression, and structural social capital on life satisfaction among people with hearing disabilities: a cross-sectional study in Shanghai, China - Wei, Xiaomin; Wang, Ting; Zhang, Yuxin; Jiang, Nan; Wang, Quqing; Cao, He; Shi, Xinrui; Wang, Jiwei (Frontiers in Psychiatry, 2023)
Background: Life satisfaction serves as a crucial indicator of social well-being and plays a significant role in formulating strategies aimed at enhancing health outcomes among the hearing-disabled population. This study aimed to examine the effect of anxiety, depression, and structural social capital on life satisfaction among people with hearing disabilities in Shanghai, China.A cross-sectional study was conducted in Shanghai, China. As of March 2022, 337 people with hearing disabilities were recruited from the Shanghai Disabled Persons' Federation. Online survey was conducted using a four-part questionnaire to collect data including demographic characteristics, the Hospital Anxiety and Depression Scale (HADS), the Social Capital Scale (SCS), and a single-item question to measure life satisfaction. One-sample t-tests, Pearson correlation analysis, and hierarchical multiple regression analysis were performed.Results: Anxiety (β = − 0.153) and depression (β = − 0.242) were significant factors influencing life satisfaction among people with hearing disabilities. Structural social capital also played an influential role in life satisfaction, people with hearing disabilities who lack social networks (β = 0.125) and social support (β = 0.121) reported significantly lower levels of life satisfaction. However, no significant 2 This is a provisional file, not the final typeset article relationship was found in this study between LS and other components of structural social capital, such as social participation.This study shows that paying attention to mental health is critical for people with hearing disabilities to achieve social well-being and promote LS improvement. At the same time, the government and society also need to focus on the structural social capital, provide various social service programs, enhance social support, and expand social networks, improving LS for people with hearing disabilities.